Production of Microalgal Biomass at Different Growth Phases to Use as Biofuel Feedstock (Journal of the Asiatic Society of Bangladesh, Science, 2021)
The growth of microalgae under optimized conditions was determined for assessing their growth rate and biomass production. In this study, the growth of both green algae (Chlamydomonas noctigama and Chlorella vulgaris) and cyanobacteria (Anabaena variabilis and Nostoc spongiaeforme) was measured as optical density. Chlamydomonas noctigama and Chlorella vulgaris showed the doubling time of 9.5 and 8.0 hours, respectively, whereas Anabaena variabilis and Nostoc spongiaeforme showed the doubling time of 14.8 and 16.6 hours, respectively. All the species exhibited the highest growth in terms of biomass at the phase in between stationary and death phases.J. Asiat. Soc. Bangladesh, Sci. 47(2): 161-171, December 2021